2017
DOI: 10.1007/s10278-017-9978-1
|View full text |Cite
|
Sign up to set email alerts
|

Performance of an Artificial Multi-observer Deep Neural Network for Fully Automated Segmentation of Polycystic Kidneys

Abstract: Deep learning techniques are being rapidly applied to medical imaging tasks—from organ and lesion segmentation to tissue and tumor classification. These techniques are becoming the leading algorithmic approaches to solve inherently difficult image processing tasks. Currently, the most critical requirement for successful implementation lies in the need for relatively large datasets that can be used for training the deep learning networks. Based on our initial studies of MR imaging examinations of the kidneys of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 125 publications
(83 citation statements)
references
References 31 publications
2
81
0
Order By: Relevance
“…Variants of these methods have been automated and validated and we expect that they will become increasingly accessible and available for disease prognostication. 29,30 Once a patient is determined to have typical ADPKD, the Mayo class should be ascertained (Figure 4). Patients in class 1A progress slowly and should not be treated.…”
Section: Step 2 Confirm the Diagnosis Of Rapidly Progressive Diseasementioning
confidence: 99%
“…Variants of these methods have been automated and validated and we expect that they will become increasingly accessible and available for disease prognostication. 29,30 Once a patient is determined to have typical ADPKD, the Mayo class should be ascertained (Figure 4). Patients in class 1A progress slowly and should not be treated.…”
Section: Step 2 Confirm the Diagnosis Of Rapidly Progressive Diseasementioning
confidence: 99%
“…Advances in computer science have created exciting new venues for complex data analyses. This includes automation, machine learning and artificial intelligence, which are rapidly being explored and integrated into medical research in nearly every field . The present study represents an early evaluation of this technology for paediatric patients with WT, which to our knowledge, has not been previously reported.…”
Section: Discussionmentioning
confidence: 94%
“…In addition, they stated that the auto technique did not require user experience or expertise for production of accurate results. Kline et al used auto‐segmentation for assessment of polycystic kidneys, and reported high accuracy. Applying fully automatic techniques for segmentation in WT seems to be an obvious next step to improve ease and efficiency of use.…”
Section: Discussionmentioning
confidence: 99%
“…Stereology is faster than planimetry but does not segment the kidney, which is a requirement for advanced image analysis. Fast, automatic segmentations, including a deep learning-based, fully automated approach capable to replace humans for the task of segmenting polycystic kidneys, have been developed (5,6). Once segmented, advanced magnetic resonance image processing and analysis, such as texture analysis, may be superior and/ or complementary to TKV in predicting or measuring disease progression (7).…”
Section: Novel Tools To Assess Prognosis and Disease Progressionmentioning
confidence: 99%